Bacteria Associated With the Leafy Salad Vegetables Of Old Dhaka City and Their Multiple Antibiotic Resistance (Mar) Index - Sen, Swagata; Saha, Mihir Lal (Dhaka University Journal of Biological Sciences, 2023)
The present work aimed to evaluate the bacteria associated with the most popular leafy salad vegetables like Coriander, Mint, and Lettuce and their antibiotic resistance pattern. Samples were collected from Rayshaheb Bazar, Nazira Bazar, and Shyam Bazar during June-August 2019. The maximum bacterial load was found in Coriander and the minimum bacterial load was in Mint. A total of 149 colonies were isolated and 35 isolates were selected for Culture and Sensitivity test against 15 common antibiotics like Amoxicillin (Ax), Cefixime (CFM), Levofloxacin (Lev), Clarithromycin (CLR), Ceftriaxone (CRO), Neomycin (N), Kanamycin (K), Ciprofloxacin (Cip), Erythromycin (E), Doxycycline (Do), Vancomycin (VA), Cefuroxime (CXM), Chloramphenicol (C), Rifampicin (RA), and Gentamycin (CN). Sixteen antibiotic resistant bacterial isolates were selected for their identification and drug resistance pattern. Among these 15 antibiotic resistant bacterial isolates, only 2 were Gram positive and were identified as Enterococcus faecalis and the Gram negative bacteria belonged to the genus Enterobacter (9), Serratia (3), Klebsiella (2).The drug resistance pattern showed that most of the isolated bacteria were resistant against Amoxicillin and susceptible to Chloramphenicol. The (multiple antibiotic resistance (MAR) inedx of the isolated bacteria ranged between 33.33% and 86.67% which is very alarming. Dhaka Univ. J. Biol. Sci. 31(2): 361-369, 2022 (July)